Performance analysis of EXP/PF and M-LWDF in downlink 3GPP LTE system - Basukala, Riyaj; Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan (Institute of Electrical and Electronics Engineers Inc., 2009)
This paper investigates the performance of exponential/proportional fair (EXP/PF) and maximum-largest weighted delay first (M-LWDF) scheduling algorithms in the third generation partnership project long term evolution (3GPP LTE) providing packet-switched multimedia services. It, then, identifies a suitable packet scheduling algorithm on a basis of their performance evaluation. The performance evaluation is conducted in terms of system throughput, average real time (RT) and non-real time (NRT) throughput, packet loss for RT service and fairness for NRT service. A video streaming traffic is used to model the RT service, while a webbrowsing traffic is modelled for NRT service. Simulation results show that at lower load M-LWDF algorithm provides better performance than EXP/PF while as the load increases the EXP/PF gives better performance.